Fenomena Culture Shock Mahasiswa Program Pertukaran Mahasiswa Merdeka Asal Sumatera Utara di Jawa - Lumbantobing, Santa; Henny I. Sitanggang; Magdalena Siahaan (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to examine the phenomenon of culture shock experienced by Merdeka Student Exchange Program students from North Sumatra who take part in study programs in Java. Culture shock is a psychological and emotional symptom that a person experiences when experiencing significant cultural changes. This study uses qualitative research methods by collecting data through in-depth interviews and participant observation. The results of this study show that students from North Sumatra experience various stages of culture shock, including the crisis stage, adjustment stage, and acculturation stage. In addition, this study also identified factors that influence the experience of culture shock, such as differences in language, food, customs, and value systems. The findings of this study are expected to provide a better understanding of the experiences of students from North Sumatra in dealing with culture shock in Java and provide guidance for relevant parties in improving support and cultural understanding for students in independent student exchange programs.